From neglect to necessity: the role of innate immunity in cutaneous squamous cell carcinoma therapy - He, Yong; Tian, Ting; Li, Yuancheng; Zeng, Yong; Wang, Xiaoke; Qian, Leqi; Tian, Tian; Jiang, Mingjun; Li, Liming (Frontiers in Immunology, 2025)
As the second most common non-melanoma skin cancer, cutaneous squamous cell carcinoma (cSCC) has experienced a significant increase in incidence. Although clinical detection is relatively easy, a considerable number of patients are diagnosed at an advanced stage, featuring local tissue infiltration and distant metastasis. Cemiplimab, along with other immune checkpoint inhibitors, enhances T cell activation by blocking the PD-1 pathway, resulting in notable improvements in clinical outcomes. Nonetheless, approximately 50% of the patients with advanced cSCC remain unresponsive to this therapeutic approach. It emphasizes the importance of finding innovative therapeutic targets and strategies to boost the success of immunotherapy across a wider range of patients. Therefore, we focused on frequently neglected functions of innate immune cells. Emerging evidence indicates that innate immune cells exhibit considerable heterogeneity and plasticity, fundamentally contributing to tumor initiation and development. The identification and eradication of cancer cells, along with the modulation of adaptive immune responses, are essential roles of these cells. Consequently, targeting innate immune cells to activate anti-tumor immune responses presents significant potential for enhancing immunotherapeutic strategies in cSCC.